(untitled) (Research, Society and Development, 2021)
The hydrogeomorphometric analysis is extremely important to understand the behavior of a hydrographic basin, making it possible to collect information about its performance in flood situations and allowing better management of the impacts resulting from rainfall. One way to obtain the parameters for this characterization is through software that simulates the responses of the system at geometric, topographic, and hydrographic levels based on an elevation model of the given region. Thus, we employed QGIS to process images obtained through the Alos Pausar radar, then refined the digital model and extracted the meaningful data with the help of the SAGA and GRASS tools. Subsequently, based on our theoretical framework, we analyzed the characteristics of the microbasin to find the cause of the flooding problems that afflict the city of Conselheiro Lafaiete, in the state of Minas Gerais, due to the overflow of Bananeiras river that crosses through the urban area of the city. However, the results showed that the microbasin of the river has characteristics that reduce the probability of flooding due to its elongated shape and good drainage.